Determinants of Corporate Social Responsibility Disclosure in the Financial Services Sector: Evidence from Gulf Cooperation Council Countries - Almutairi, Zaid Matar (Curtin University, 2022)
This study investigates the determinants of Corporate Social Responsibility (CSR) disclosure in Gulf Cooperation Council (GCC) listed financial firms. It builds on a growing literature investigating the role and determinants of corporate responsibility and sustainability disclosure in accounting reporting, but is unique in its focus on the GCC, and particularly its financial services sector. It further investigates the differences in the extent and determinants of CSR disclosure between Islamic and conventional listed financial firms in the GCC.